Scrutiny or Complacency? Banking Union in the Bundestag and the Assemblée Nationale - Högenauer, Anna-Lena (2021)
The financial and eurozone crises highlighted the inadequacy of the original governance structures of the eurozone. In response, a range of reforms were launched, including the creation of a European banking union. In practice, some elements of the banking union were delayed by division among member states and the breakdown of the Franco-German motor, such as the question of the operationalization of the single resolution mechanism and fund or the deposit insurance scheme. In addition, eurozone governance—which would once have been regarded as a technocratic issue—became increasingly politicized. The aim of this article is to study the extent to which the banking union was scrutinized by parliament and to what degree this reflects material interests and ideas. For this purpose, it focuses on salience (i.e., how much attention the issue received) and polarization (i.e., the divergence of positions). The analysis of the resolutions and debates of the German Bundestag and French Assemblée Nationale, i.e., the parliaments of two key states in EU decision-making on banking union, finds that the German government was indeed closely scrutinized, whereas the French government was relatively unconstrained.